Independence of Deaf Students Through Mesatue Method Using Cartoon Media In Hindu Religious Learning - Desak Putu Saridewi; Yupin Aungsuroch; I Gede Juanamasta (Journal of Education Technology, 2023)
Deaf children face problems with independence. The attitude of independence has a very positive impact on their daily lives. This study aims to analyze the cartoon media mesatue method in the Hindu religious confidence of students with disabilities. This type of research is development. The research method of developing media uses the 4D model, including the define, design, development, and dissemination stages according to the characteristics of students with hearing impairments. The data collection used is the observation method, with the instrument aspects of student independence, interviews, and in-depth documentation. The analysis in this study uses a qualitative descriptive method that focuses on how to increase the independence of deaf students in learning Hinduism. This research was conducted with an initial evaluation before using cartoon media and a final evaluation after watching Hindu religious education. The research for the deaf category showed that the introduction of Hindu religious values by the mesatue method with cartoon media reached 72% for the elementary level, the junior high school increased by 58%, and high school by 97% with a total of 16 students. Interactive image displays can accommodate deaf students. It was concluded that the mesatue method with cartoon media could increase student independence according to the indicators formulated in the learning objectives.